Mathematical description of TCP-sessions using AQM-algorithms for nonlinear packet drop model - Starkova, Olena; Andrushko, Dmytro (Видавництво Львівської політехніки, 2012)
In this paper a mathematical description of TCPsessions using AQM-algorithms for nonlinear packet drop model is proposed. The novelty of the model is that it makes it possible to describe the dynamics of multiflow data exchange based on AQM/TCP-algorithms.
Keywords: TCP-sessions; AQM; NGN